Kajian Kesedaran Kaedah Pengasingan Sisa Pepejal Pembinaan di Tapak Pembinaan - Mohd Fuzi, Nurfatin; Abd Rahim, Mohd Hilmi Izwan; Zainal, Rozlin (Research in Management of Technology and Business, 2023)
The construction is the most important sector in Malaysia that contributes to the country’s economic development because it provides employment opportunities in various fields. However, it also contributes negative effects to the environment such as landslides, soil erosion, and soil deposition, construction waste and others. Therefore, the objective of this study is to examine the factors that contribute to the failure of construction solid waste segregation methods at construction sites and to study methods to increase awareness of construction solid waste segregation at construction sites. The study focused on the awareness of construction solid waste segregation methods at construction sites. Then, respondent involved G7 contractors registered in Johor which are 695 people, and the sample size is 248 people, SW Corp Malaysia is represented by one person and the Local Authority which has 16 with a sample size of 14 people. Quantitative methods are used for data collection by distributing questionnaires to respondents and the response rate was 38% of the total number (263 people) which is 100 respondents given feedback. This study brings importance in the construction industry by ensuring that a systematic construction solid waste segregation system can be implemented to minimize construction waste and construction costs. Research results for the factors that contribute to the failure of construction solid waste segregation methods at construction sites are expected to be overcome and methods to increase awareness of construction solid waste segregation at construction sites are also recommended more effectively. In conclusion, this study is expected to be practice construction solid waste segregation methods to increase awareness of construction solid waste segregation at construction sites.